Business Feasibility Study Reviewed From Market and Marketing Aspects in the Digital Invitation Business Kekondangan.Id - Nasution, Mutiara Akbar; Fitri, Anisa; Safitri, Nurdina (Economic: Journal Economic and Business, 2023)
This study aims to analyze the feasibility of the business run by Kekondangan.id in terms of market and marketing aspects. This research is a study conducted with qualitative methods using online interview data collection techniques with parties concerned with Kekondangan, id. The results of the business feasibility analysis in terms of market and marketing aspects are said to be feasible because Kekondangan.id has many successful promotional strategies implemented, has attractive brands and name identities, has affordable prices for all the conveniences provided. Kekondangan.id stated that they are Winning Campaign with evergreen business, or the term is timeless because digitalization in the future is more needed than conventional.